Cloning of Soluble Human Stem Cell Factor in pET-26b(+) Vector - Salman Asghari; Mahmoud Shekari Khaniani; Masood Darabi; Sima Mansoori Derakhshan (Tabriz University of Medical Sciences, 2014)
Purpose: Stem cell factor (SCF) plays an important role in the survival, proliferation and differentiation of hematopoietic stem cells and progenitor cells. Potential therapeutic applications of SCF include hematopoietic stem cell mobilization, exvivo stem/progenitor cell expansion, gene therapy, and immunotherapy. Considering the cost and problem in accessibility of this product in Iran, clears the importance of indigenizing production of rhSCF. In the present work, we describe the construction of the soluble rhSCF expression vector in pET-26b (+) with periplasmic localization potential. Methods: Following PCR amplification of human SCF ORF, it is cloned in pET-26b (+) vector in NcoI and XhoI sites. The recombinant construct was transformed into BL21 (DE3) Ecoli strains. Results: The construction of recombinant vector was verified by colony PCR and sequence analysis of pET26b-hSCF vector. Sequence analyses proved that human SCF ORF has been inserted into NcoI and XhoI site with correct orientation downstream of strong T7 promotor and showed no nucleotide errors. Conclusion: The SCF ORF was successfully cloned in pET-26b (+) expression vector and is ready for future production of SCF protein.